Extension of Cap by Size and Degree in the Space PG(3,11)‎ - Jabbar Sharif Radhi; Emad Bakr Al-Zangana (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
A cap of size  and degree  in a projective space, (briefly; (k,r)-cap) is a set of  points with the property that each line in the space meet it in at most  points. The aim of this research is to extend the size and degree of complete caps and incomplete caps, (k, r)-caps of degree r